Large scale chemical synthesis, purification and crystallization of RNA-DNA chimeras. - Usman, N (Nucleic Acids Res, 1992)
RNA-DNA chimeras, in which both DNA and RNA monomers are site-specifically substituted in the same strand, may be prepared only by chemical synthesis. Biochemical studies have revealed a number of surprising and subtle effects resulting from the insertion of either a ribonucleotide into a DNA strand or a deoxyribonucleotide into an RNA strand. The availability of large quantities of these chimeras allows for their crystallization and subsequent x-ray structure determination. We describe a flexible and efficient method for the large-scale preparation of these compounds, their purification, and their crystallization. The methodology is based on a combination of existing DNA phosphoramidite synthons and those recently introduced for the preparation of biochemically active RNA1. We demonstrate that these two different synthons are compatible, produce large quantities of nucleic acid needed for physical studies, and that high resolution diffraction quality crystals may be grown from these chimeras. Of the duplex chimeras synthesized and crystallized, [r(G)d(CGTATACGC)]2, [d(GCGT)r(A)d(TACGC)]2 and [r(GCG)d(TATACCC) + d(GGGTATACGC)] form A-helices and d(CG)r(CG)d(CG)]2 forms a left-handed Z-helix. IMAGES: